Harnessing cognitive strategy use for functional problems and proposed underlying mechanisms in childhood-onset dystonia. (November 2022) - Butchereit, Kailee; Manzini, Michael; Polatajko, Helene J.; Lin, Jean-Pierre; McClelland, Verity M.; Gimeno, Hortensia
Abstract: Background: There is a significant gap in knowledge about rehabilitation techniques and strategies that can help children and young people with hyperkinetic movement disorders (HMD) including dystonia to successfully perform daily activities and improve overall participation. A promising approach to support skill acquisition is the Cognitive Orientation to daily Occupational Performance (CO-OP) intervention. CO-OP uses cognitive strategies to help patients generate their own solutions to overcome self-identified problems encountered in everyday living. Purpose: 1. To identify and categorize strategies used by children with HMD to support skill acquisition during CO-OP; 2. To review the possible underlying mechanisms that might contribute to the cognitive strategies, in order to facilitate further studies for developing focused rehabilitation approaches. Methods: A secondary analysis was performed on video-recorded data from a previous study exploring the efficacy of CO-OP for childhood onset HMD, in which CO-OP therapy sessions were delivered by a single occupational therapist. For the purpose of this study, we reviewed a total of 40 randomly selected hours of video footage of CO-OP sessions delivered to six participants (age 6–19 years) over ten intervention sessions. An observational recording sheet was applied to identify systematically the participants' or therapist's verbalizations of cognitive strategies during the therapy. The strategies were classified into six categories in line with published literature. Results: Strategies used by HMD participants included distraction, externally focussed attention, internally focussed attention, emotion self-regulation, motor imagery and mental self-guidance. We postulate different underlying working mechanisms for these strategies, which have implications for the therapeutic management of children and young people with HMD including dystonia. Conclusions: Cognitive strategy training can fundamentally change and improve motor performance. On-going work will address both the underlying neural mechanisms of therapeutic change and the mediators and moderators that influence how change unfolds. Highlights: Cognitive strategy use can support skill acquisition in childhood-onset hyperkinetic movement disorders (HMD). Childhood-onset HMD may benefit from CO-OP and cognitive rehabilitation strategies. Useful cognitive strategies included distraction, external and internal-focussed attention, and motor imagery.